Employing Fuzzy Delphi technique to validate Multiple Intelligence based Instructional Teaching Module for preschool children - Abdul Rahman, Fadzilah Bee; Mustafa, Zaida; Kharuddin, Azrul Fazwan (Southeast Asia Early Childhood Journal, 2021)
Delphi method which is a technique and structured approach used to review and collect opinions of a group of experts, has its own weaknesses. The Fuzzy Delphi Method (FDM), derived from modifications of Delphi Method introduced by Kaufman and Gupta in 1988, is considered by many researchers as more superior in providing evidence of human linguistic system (which is the signature of Delphi Technique). In this paper, FDM was used to assess the key components and contents of an instructional module based on multiple intelligences (MI-Based Instructional Module). This development phase is part of a project to develop a MI-Based Instructional Module for 4 years old preschool children in Malaysia. This phase involves the views of 10 experts who are experienced in teaching preschool children and have deep knowledge in early childhood education. It is a rigorous statistical analysis to validate the validity of abstract concept of the MI-Based Instructional Module. Experts are required to validate the key components and contents of the MI-Based Instructional Module which include themes, sub-themes based on Bloom’s taxonomy, learning objectives, learning activities based on higher order thinking skills, multiple intelligence component and assessment for learning using seven-point linguistic before converting into triangular fuzzy numbers (TFNs). The validity of these key components and contents to make up the instructional module for 4 years old preschool children is very crucial to provide good learning experiences for learners that could enhance their innate potential; thus, FDM was used to provide evidence of validity of the instructional module. This article presents the results of the experts’ views and the appropriateness of FDM as a tool to provide information about the validity of a MIBased Instructional Module.